Going Off, Growing Strong: A program to enhance individual youth and community resilience in the face of change in Nain, Nunatsiavut - Hirsch, Rachel; Furgal, Chris; Hackett, Christina; Sheldon, Tom; Bell, Trevor; Angnatok, Dorothy; Winters, Katie; Pamak, Carla (Études/Inuit/Studies, 2016)
Dispossession from social and ecological support systems is a major concern for many Indigenous communities. In response to community health challenges in these settings a number of initiatives such as youth mentorship programs have shown some value in enhancing adaptive capacity. The pilot Going Off, Growing Strong program provides opportunities for at-risk youth to engage in community- and land-based activities and build relationships with positive adult role models in Nain, Nunatsiavut (Labrador, Canada). This paper offers an interpretive description drawing from autobiographical accounts of the development of this innovative program. A collaboratively developed conceptual framework, based on the literature, is used to present and explain program operator’s experiences and rationale for program development. The emergent goals of Going Off, Growing Strong are to strengthen individual youth and collective community resilience through intergenerational exchange of land, social, and cultural skills and knowledge by drawing on social supports, such as a community freezer and experienced harvesters. We found that the process of collaborating over time with multiple stakeholders in creating this conceptual framework was an important one for solidifying the goals of Going Off, Growing Strong and creating context-specific, meaningful evaluation outcomes to enable future measurement of impacts on the community.